The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pr8111342
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki–Miyaura Reactions of (4-bromophenyl)-4,6-dichloropyrimidine through Commercially Available Palladium Catalyst: Synthesis, Optimization and Their Structural Aspects Identification through Computational Studies

Abstract: 5-(4-bromophenyl)-4,6-dichloropyrimidine was arylated with several aryl/heteroaryl boronic acids via the Suzuki cross-coupling reaction by using Pd(0) catalyst to yield novel pyrimidine analogs (3a-h). It was optimized so that good yields were obtained when 5 mol % Pd(PPh3)4 was used along with K3PO4 and 1,4-Dioxane. Electron-rich boronic acids were succeeded to produce good yields of products. Density functional theory (DFT) calculations were also applied on these new compounds to analyze their reactivity des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…and 9048.28 a.u., respectively, showing the highest NLO responses, while the remaining compounds show very small hyperpolarizability values. Our research group reported N-heterocyclic derivatives having smaller values of hyperpolarizability as compared to the compounds in this study ( 4a – 4n ) [ 34 ].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…and 9048.28 a.u., respectively, showing the highest NLO responses, while the remaining compounds show very small hyperpolarizability values. Our research group reported N-heterocyclic derivatives having smaller values of hyperpolarizability as compared to the compounds in this study ( 4a – 4n ) [ 34 ].…”
Section: Resultsmentioning
confidence: 93%
“…From the computational point of view, these methods have become very popular in recent years because they can attain similar accuracy to the ab initio methods in less time and at a lower computational cost [ 33 ]. The optimization of the molecules ( 4a – 4n ) was accomplished with the PBE0-D3BJ/def2-TZVP/SMD 1,4-dioxane level of theory [ 34 ] which is widely used for providing accurate geometries and electronic properties for a large number of molecules. The solvent model density (SMD) is a polarizable continuum model that includes the full solute electron density without defining partial atomic charges.…”
Section: Resultsmentioning
confidence: 99%
“…The new structures are combinations of pyrimidine–hydrazone, dihydronaphthalene and alkylamine chain groups. Pyrimidine is a well-known aromatic, heterocyclic organic compound with many different biological functions [ 3 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The product from the reaction mixture was purified by CC. The synthesized product was analyzed by 1 H-NMR, 13 C-NMR, and elemental analysis [30,31]. The 5-bromo-N-(5-methyl-pyrazol-3-yl)thiophene-2-carboxamide (1 eq.…”
Section: Synthesis Of N-(5-methyl-1h-pyrazol-3-yl)-5-(p-tolyl)thiophene-2-carboxamide (8b)mentioning
confidence: 99%